Wheelchair propulsion: effects of experience and push strategy on efficiency and perceived exertion - Lenton, J. P.; Fowler, N. E.; van der Woude, L.; Goosey-Tolfrey, V. L. (Applied Physiology, Nutrition, and Metabolism, 2008)
The purpose of this study was to examine the role of wheeling experience on efficiency, metabolic cost, and differentiated ratings of perceived exertion (RPEs) during synchronous and asynchronous hand-rim propulsion with varying arm frequencies. Fourteen able-bodied (AB) male participants and 8 male wheelchair sportsmen (WS) performed tests of peak oxygen consumption for both propulsion modes. Subsequently, 2 series of five 4-min sub-maximal exercise bouts were completed at an individualized velocity (60% of peak oxygen consumption). Arm frequencies consisted of the freely chosen frequency (FCF), followed by 4 counter-balanced paced trials pushing at 60%, 80%, 120%, and 140% of the FCF. Efficiency indices (gross, GE; work, WE) were determined and peripheral (RPE-P), central (RPE-C), and overall (RPE-O) RPEs were recorded. The GE (6.4% vs. 8.4%) and WE (11.3% vs. 15.1%) were significantly higher in WS than in AB (p = 0.001). Trends in the oxygen consumption, GE, and WE data were similar in both groups, propulsion mode, and arm frequency. Data suggest that 80% FCF resulted in improved efficiency for both propulsion mode and group, although the differences between those arm frequencies immediately above and below were non-significant. Lower RPE scores corresponded with higher efficiency values. Regardless of group there were significant differences (p = 0.001) between the differentiated RPE measures, whereby RPE-P was on average always the highest score (13.1) and RPE-C the lowest (11.1; RPE-O was 12.2). In conclusion, despite the anticipated differences in efficiency between the WS and AB participants, this study confirmed that psycho-physiological measures produce similar trends to physiological measures with manipulations of both arm frequency and propulsion mode.